Time networks: history and synchronicity in contemporary Croatian cinema - Janica, Tomić (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The paper demonstrates the prominence of network narratives (films with several autonomous storylines, globally popular since the mid-1990s) in post-Yugoslav, particularly Croatian, cinema, with examples such as Metastases (2009), The Reaper (2014), You Carry Me (2015), The Constitution (2016), The Trampoline (2017), etc. Unlike network narratives elsewhere, these films often thematize history, with parallel stories typically set during World War II and the Yugoslav Wars of the 1990s. This has been said to suggest as a circular, synchronic vision of history, a “transhistorical dance macabre” as a leitmotif of Balkan cinema. The films Witnesses (2003) and The High Sun (2015), together with a group of multi-narrative plays, i.e. The Last Link (1994), 3 Winters (2014) and Men of Wax (2016), are analysed as vehicles of counter-memory to such self-Balkanizing representations.